Chapter 36 Current States, Challenges, and Opportunities of the Intelligent Tutoring Systems (ITS) in Developing Countries in Asia - Kumar Bhagat, Kaushal (Taylor & Francis, 2018)
This chapter provides an overview of ITS-related research undertaken in Asian developing countries. The chapter begins with a brief overview of the development and nature of ITSs. It then outlines the methods for selecting and analyzing the literature used for the study, describing the research foci of these studies and highlighting the findings in relation to the effectiveness of ITSs developed or deployed in these countries. The chapter concludes with a discussion of the limitations of current ITS research and identifies potential areas for further study.